Simple Progression Law in Predicting the Damage Onset and Propagation in Composite Notched Laminates - Suhairil Meon, Mohd; Rao Mekala, Narasimha; Schroeder, Kai-Uwe S (International Journal of Engineering and Technology, 2018)
The aim of this article is to simulate the damage initiation and progression in unidirectional (UD) laminates. A three-dimensional (3D) failure criteria of Puck incorporated with degradation scheme is developed. Two types of degradation law known as sudden degradation are used to predict the damage progression in UD laminates. The establishment of constitutive law in progressive damage model (PDM) is achieved through implementation of user subroutines in Abaqus. The failure analysis is applied to various composite stacking sequences and geometries, as well as different fiber reinforced polymer (FRP) composite materials. The comparative studies revealed that the predicted ultimate failure load agree well with those available in the literature.Â